Alternative reproductive modes of Atlantic forest frogs - Toledo, Luis Felipe; Garey, Michel V.; Costa, Thais R. N.; Lourenco-de-Moraes, Ricardo; Hartmann, Marilia T.; Haddad, Celio Fernando Baptista [UNESP] (Springer Tokyo, 2012)
Diversity in reproductive modes is well known in amphibians, mainly among anurans, which are characterized by a diversity in breeding biology that exceeds that of any other tetrapod. Currently, 39 reproductive modes are recognized among anurans and some species display more than one mode. The breeding biology of some Brazilian Atlantic forest anurans was investigated for this study. We observed unreported reproductive modes for six species, variability in the reproductive modes of individuals of the same species (whereby some individuals of a given population displayed unusual reproductive modes when the physical conditions of the breeding site were suboptimal), and variations within the modes. These observations suggest possible evolutionary steps for the reproductive modes. Anuran breeding biology seems to be more diverse than previously reported, and a character matrix could be constructed to describe the total range of variation of the anuran reproductive modes.
Keywords: Reproduction; Amphibian; Anura; Behavioral variation; Egg-deposition site